The Impact of Government Size on Financial Development: A Global Perspective - Balasubramaniam, Arunnan; Lee, Chin; Law, Siong Hook (Advances in Social Sciences Research Journal, 2026)
This study investigates the linear effects of government size on financial development using a balanced panel of 71 countries from 1995 to 2021. Government size was measured using the commonly used general government final consumption expenditure as percentage of GDP (%), while financial development is proxied by private credit and deposit money bank assets (each as % of GDP). The estimation in this study relies on a dynamic system generalized methods of moments (GMM). The main result indicates that government size does not have a statistically significant impact on financial development at the global level. This study concludes that one-size-fits-all approach may not be effective. The results provide no conclusive support for either the political view or the development view.